Effect of acute mild hypoxia during exercise on plasma free and sulphoconjugated catecholamines - Strobel, Günther; Neureither, Marcus; Bärtsch, Peter (European journal of applied physiology, 1996)
Catecholamine (CA) response to hypoxic exercise has been investigated during severe hypoxia. However, altitude training is commonly performed during mild hypoxia at submaximal exercise intensities. In the present study we tested whether submaximal exercise during mild hypoxia compared to normoxia leads to a greater increase of plasma concentrations of CA and whether plasma concentration of catecholamine sulphates change in parallel with the CA response. A group of 14 subjects [maximal oxygen uptake, 62.6 (SD 5.2) ml · min−1 · kg−1 body mass] performed two cycle ergometer tests of 1-h duration at the same absolute exercise intensities [191 (SD 6) W] during normoxia (NORM) and mild hypoxia (HYP) followed by 30 min of recovery during normoxia. Mean plasma concentrations of noradrenaline ([NA]), adrenaline ([A]), and noradrenaline sulphate ([NA-S]) were elevated (P < 0.01) after HYP and NORM compared with mean resting values and were higher after HYP [20.9 (SEM 3.1), 2.2 (SEM 0.24), 8.12 (SEM 1.5) nmol · 1−1, respectively] than after NORM [(13.7 (SEM 0.9), 1.5 (SEM 0.14), 6.8 (SEM 0.7) nmol · 1−1, respectively P < 0.01]. The higher plasma [NA-S] after HYP (P < 0.05) were still measurable after 30 min of recovery. From our study it was concluded that exercise at the same absolute submaximal exercise intensity during mild hypoxia increased plasma CA to a higher extent than during normoxia. Plasma [NA-S] response paralleled the plasma [NA] response at the end of exercise but, in contrast to plasma [NA], remained elevated until 30 min after exercise.